Pesticide Residues In Selected Vegetable Collected From Wet Markets Of Bangladesh - Hasan, Mehedi; Rahman, Azizur (Advances in Social Sciences Research Journal, 2019)
Pesticide residues in vegetable have become a major concern associated with food safety issues. Translocation of pesticides in selected vegetable samples was determined using gas chromatography-mass spectrophotometry (GC-MS) procedures and quick, easy, cheap, effective, rugged and safe (QuEChERS) method with acetate buffering (AOAC Official Method 2007.01) was used for sample preparation. Pesticide residues above the maximum residue levels (MRLs) were found in 3 brinjal, 2 country bean and 1 tomato samples. The result revealed that country bean collected from Karwanbazar, Dhaka and Jessore sadar wet market contained 44.92 µg/kg and 38.65 µg/kg Dimethoate residue, respectively. Brinjal sample collected from Jatrabari, Dhaka, Khetlal bazar and Mithapukur bazar wet market contained 32.54 µg/kg, 25.82 µg/kg and 20.65 µg/kg Quinalphos residue respectively. Tomato sample collected from Narsingdi sadar wet market contained 8.50 µg/kg Quinalphos residue, which was lower than Maximum Residue Levels (10 µg/kg).